Antibiotic resistance and molecular identification of dominant bacteria associated with loose shell syndrome in mangrove crabs (Scylla spp.) - Villarias Ma. Patricia; Gabuat Hans Gabriel; Romey Maria Theresa; Pakingking Rolando; Ynion Gene Philip Levee; Fagutao Fernand; Suharman Indra; Caipang Christopher Marlowe (BIO Web of Conferences, 2024)
The emergence of loose shell syndrome (LSS) in Philippine mangrove crabs poses a serious threat to both the aquaculture industry and the delicate ecosystems it relies on. This study aimed to identify dominant bacteria associated with LSS and assess their antibiotic resistance to guide treatment and prevention strategies while safeguarding public health. Mangrove crab samples with loose carapace were collected from the province of Capiz, Philippines. Dominant bacteria that grew on Thiosulfate– Citrate–Bile Salts–Sucrose (TCBS) and modified chitin agar were isolated and identified by sequencing of the16S rRNA. Antibiotic susceptibility of the dominant bacterial isolates was performed using the agar disk diffusion method. Dominant bacteria that grew on TCBS agar included putative Vibrio, Proteus, Shewanella, and Stutzerimonas. The isolates had antibiotic resistance indices (ARI) ranging 0.8 to 1.2. Chitinolytic bacteria were dominated by Vibrio, Shewanella, and Brevundimonas. Both Vibrio and Brevundimonas exhibited resistance to gentamicin, ciprofloxacin, and norfloxacin, while Shewanella showed resistance to ciprofloxacin. The presence of multi-drug resistant bacteria in LSS-affected crabs highlights the urgent need for effective health management strategies in the industry while mitigating the risks associated with antibiotic resistance to protect both the sustainability of mangrove crab aquaculture and the health of consumers.